"EINLEITUNG IN DAS NEUE TESTAMENT" AUS PATRISTISCHER PERSPEKTIVE = “INTRODUCTION TO THE NEW TESTAMENT” FROM A PATRISTIC PERSPECTIVE - Meiser, Martin (Sacra scripta, 2023)
This article presents the genres of ancient Christian exegesis and envisages patristic exegesis with regard to questions of "Introduction in the New Testament" (authorship, dating, localizing, adversaries, stylistic characteristics). Identifications of the authors with biblical persons are prevalent; no extratextual framing is important. Comparable with modern exegesis are the method of temporal ordering the Pauline epistles, the stylistic comparison between the Gospel of John and the Apocalypse, sometimes also the description of adversaries refuted in the Pauline and Catholic Epistles.